1989
DOI: 10.1111/j.1365-3083.1989.tb01147.x
|View full text |Cite
|
Sign up to set email alerts
|

The Modulatory Effect of Lipoproteins on the Release of Interleukin 1 by Human Peritoneal Macrophages Stimulated with β‐1,3‐d‐Polyglucose Derivatives

Abstract: Human peritoneal macrophages were stimulated in vitro with beta-1,3-D-polyglucose-derivatized microbeads (GDM) or soluble aminated beta-1,3-D-polyglucose (AG) in combination with lipoproteins. The release of interleukin 1 (IL-1) was analysed in cell supernatants in a thymocyte proliferation assay. We report that the release of IL-1 is markedly enhanced in macrophages stimulated with polyglucose in either form in combination with native low-density lipoprotein (LDL) or acetyl LDL at a concentration of 100 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Furthermore, the production of TNF‐α in the subgroup of diabetic patients treated with the cholesterol‐lowering drug simvastatin did not differ from that of the healthy control subjects. This is consistent with earlier in vitro studies, which showed that addition of serum lipids to macrophage cultures inhibited cytokine release [28, 29]. At the same time, a pleiotropic effect of simvastatin cannot be excluded, because the addition of the drug directly to cultures of human monocytes dramatically augments LPS‐stimulated production of TNF‐α and other cytokines in these cells [30].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the production of TNF‐α in the subgroup of diabetic patients treated with the cholesterol‐lowering drug simvastatin did not differ from that of the healthy control subjects. This is consistent with earlier in vitro studies, which showed that addition of serum lipids to macrophage cultures inhibited cytokine release [28, 29]. At the same time, a pleiotropic effect of simvastatin cannot be excluded, because the addition of the drug directly to cultures of human monocytes dramatically augments LPS‐stimulated production of TNF‐α and other cytokines in these cells [30].…”
Section: Discussionsupporting
confidence: 89%
“…The unusually strong and rapid IL-I release brought about by AG (significanily stronger than by LPS [17]) suggests a role for IL-I in AGmediated lutnour necrosis. Nakamura ct al.…”
Section: Discussionmentioning
confidence: 96%
“…Although oxLDL has been known to trigger IL-1β production in foam cells 48, 49, 50 , many of these studies were carried out before identification of the NLRP3-inflammasome. Our work provides the molecular mechanism for how oxLDL induces macrophage secretion of IL-1β by showing that CD36 binding of this ligand controls its engagement of the two necessary pathways for full inflammasome activation: Signal 1 via the TLRs and Signal 2 via the NLRs.…”
Section: Discussionmentioning
confidence: 99%